Narrative Analysis of Entertainment World Criticism on Pretty Boys Film - Rashid Ridha; Poppy Febriana (Universitas Muhammadiyah Sidoarjo, 2022)
Film is a product of innovation from the media. In the film there are educational values, information, persuasion and entertainment that have meaning for the viewer. Films can also be a means for filmmakers to convey messages in the form of storylines and then turn them into scenes in the narrative. The researcher discusses the analysis of narrative and dialogue in the film